Acupuncture Dosage and Its Correlation with Effectiveness in Patients with Chronic Stable Angina: A Systematic Review and Meta-Analysis of Randomized Controlled Trial - Huang D; Li Y; Zheng X; Hu J; Tang H; Yin Y; Wu Z; Kong L (Journal of Pain Research)
Dajun Huang,1,* Yanwei Li,1,* Xiaoyan Zheng,2,3,* Jinming Hu,1 Hanzhang Tang,1 Yongjun Yin,1 Zhou Wu,1 Lingqiu Kong1 1Department of Cardiovascular Medicine, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, People’s Republic of China; 2Clinical Research Center for Acupuncture and Moxibustion in Sichuan province, Sichuan JinXin Xinan Women’s and Children’s Hospital, Chengdu, People’s Republic of China; 3Acupuncture and Tuina School, Chengdu University of Traditional Chinese Medicine, Chengdu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lingqiu Kong; Zhou Wu, Department of Cardiovascular Medicine, Hospital of Chengdu University of Traditional Chinese Medicine, Address: No. 39 Shi’er Qiao Road, Chengdu, Sichuan, 610023, People’s Republic of China, Email klq521@163.com; 1209293923@qq.comObjective: This systematic review aimed to compare the efficacy of various acupuncture dosages for Chronic Stable Angina (CSA) using randomized controlled trials (RCTs), addressing the unclear relationship between dosage and effectiveness despite acupuncture’s potential.Methods: We searched eight bibliographic databases from inception to October 31, 2024, evaluating RCTs comparing acupuncture to placebo or standard care for CSA patients, focusing on angina attack frequency as the primary outcome. Studies were categorized into high (HDG), moderate (MDG), and low (LDG) dosage groups based on acupuncture characteristics: the number of acupoints, total sessions, frequency per week, and the need for “Deqi”.Results: Of the 807 citations screened, 16 studies (1240 patients) were included: 3 studies in LDG, 10 in MDG, and 3 in HDG. Acupuncture significantly reduced angina attacks compared to placebo (SMD, − 0.51; 95% CI [− 0.77, − 0.25], P = 0.0001, I2=62%), and standard care (SMD, − 1.25, 95% CI [− 1.89, − 0.61], P = 0.00001, I2=92%) without increasing adverse events. MDG showed a notable difference in reducing angina attacks (SMD, − 0.60, 95% CI [− 0.91, − 0.29], P = 0.001, I2=60%) while LDG and HDG did not. There is no difference in adverse events between groups. The evidence quality ranged from very low to moderate, and the results should be cautiously applied.Conclusion: Acupuncture therapy effectively and safely alleviates CSA symptoms. Moderate dosage demonstrated the potential for better effects in reducing symptoms, suggesting optimal dosage considerations for future treatments.Prospero Registration Number: CRD42022321547.Keywords: acupuncture, chronic stable angina, dose-related, effectiveness, meta-analysis